Transfer of 50 thousand improved genetically improved farmed tilapia (GIFT) fry to Nigeria - Trinh, Trong (WorldFish, 2023)
The data contains the list of female broodstock that produced improved GIFT fry sent to Nigeria in three batches in 2022